PELAYANAN STIMULASI DETEKSI INTERVENSI DINI TUMBUH KEMBANG PADA SISWA BUNDA MULIA SCHOOL JAKARTA UTARA - Wiyarni Pambudi; Fitri Aqila; Desi Natalia (Jurnal Bakti Masyarakat Indonesia, 2023)
Successful indicators of fostering child growth and development are not only improving children's health andnutritional status but also developing children's mental, emotional, social and independence optimally. Earlydetection of growth and development deviations needs to be carried out in order to find out the possibility ofdeviations including following up on any parents' complaints about child development problems. The service ofStimulation, Detection, Early Intervention for Growth and Development (SDIDTK) was provided to 65 (87.8%)students of Bunda Mulia School, involving clerkship students of the Resident Program for anthropometricexaminations in the form of measuring body weight and height. Parents of students were asked to cooperate in fillingg-form questions with the Developmental Pre Screening Questionnaire (KPSP) and the Emotional Behavior ProblemQuestionnaire (KMPE). Assessment of examination data shows the status of individual growth and development,which needs to be followed by stimulation or intervention ef orts according to the needs of each child. Growthscreening showed 58 ( 89.2%) of students had good nutritional status, although there were still students withoverweight status, obesity, and short stature. Developmental screening found 55 (93.2%) students withage-appropriate KPSP assessments and 50 (84.7%) results KMPE is normal. Clean and healthy living habitsinclude feeding rules, dental and oral health care, prevention of Influenza Like Illness-Severe Acute RespiratoryInfection (ILI-SARI), hearing, vision and daily sleep patterns are not yet fully can be applied well by Playgroup,Pre-Kindergarten, Kindergarten-1, and Kindergarten-2 students. ABSTRAK Indikator keberhasilan pembinaan tumbuh kembang anak tidak hanya meningkatnya status kesehatan dan gizi anaktetapi juga mental, emosional, sosial dan kemandirian anak berkembang secara optimal. Deteksi dini penyimpangantumbuh kembang perlu dilakukan guna mengetahui adanya kemungkinan penyimpangan termasuk menindaklanjutisetiap keluhan orang tua terhadap masalah tumbuh kembang anak. Pelayanan Stimulasi, Deteksi, Intervensi DiniTumbuh Kembang (SDIDTK) diberikan kepada 65 (87,8%) siswa Bunda Mulia School, melibatkan mahasiswakepaniteraan Program Studi Profesi Dokter untuk pemeriksaan antropometri berupa pengukuran berat badan dantinggi badan. Orangtua siswa diminta kerjasamanya mengisi g-form pertanyaan Kuesioner Pra SkriningPerkembangan (KPSP) dan Kuesioner Masalah Perilaku Emosional (KMPE). Asesmen data pemeriksaanmenunjukkan status pertumbuhan dan perkembangan secara individual, yang perlu diikuti upaya stimulasi atauintervensi sesuai kebutuhan masing-masing anak. Skrining pertumbuhan menunjukkan 58 (89,2%) siswa berstatusgizi baik, walaupun masih dijumpai siswa dengan status gizi lebih, obesitas, dan perawakan pendek. Skriningperkembangan mendapati 55 (93,2%) siswa dengan asesmen KPSP sesuai usia dam 50 (84,7%) hasil KMPE normal.Kebiasaan perilaku hidup bersih dan sehat antara lain aturan makan (feeding rules), perawatan kesehatan gigi danmulut, pencegahan Influenza Like Illness-Severe Acute Respiratory Infection (ILI-SARI), daya dengar, daya lihat danpola tidur harian belum sepenuhnya dapat diterapkan dengan baik oleh siswa Playgroup, Pre-Kindergarten,Kindergarten-1, dan Kindergarten-2.